Semi-liquid surface with liquid-solid repellency
Through the formation of the PDMS polymer graft layer, the problem of poor surface durability of liquid repulsion in the prior art is solved, and the durable liquid repulsion under high temperature and wear conditions is achieved, which significantly improves the stability of the surface treatment.
Patent Information
- Application Number
- CN202080059193.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-19
- Filing Date
- 2020-06-09
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-06-09
AI Technical Summary
Existing surface treatment methods are difficult to maintain liquid repulsion for a long time, and are often failed due to loss of air or liquid lubricant or surface damage, and lack a long-lasting liquid repulsion surface.
By treating the substrate surface with polydimethylsiloxane (PDMS) oligomer, a PDMS polymer graft layer is formed, and a durable liquid repulsive surface is formed by covalent bonding of the hydroxylated surface with the PDMS oligomer.
It realizes the maintenance of liquid repulsion under harsh conditions such as high temperature, wear and scratches, significantly improves the durability and stability of surface treatment, and surpasses the performance of traditional liquid injection surfaces and superhydrophobic surfaces.
Smart Images

Figure CN114341235B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority under 35 U.S.C. §119(e) to U.S. Provisional Application No. 62 / 863,535, filed on June 19, 2019, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] The present application generally relates to methods of treating surfaces to enhance liquid repellency and the treated surfaces themselves, and more particularly to methods of treating substrate surfaces with polydimethylsiloxane (PDMS) oligomers to form a PDMS polymer grafted layer on the surface, and articles having such a grafted layer. Background Art
[0004] Solid surfaces are treated so that they can better repel liquids and receive extensive attention. Current surface treatment methods include forming super-hydrophobic or super-oleophobic surfaces that rely on air lubricants, or liquid injection surfaces that rely on liquid lubricants. However, such treated surfaces often lack persistence, for example due to air or liquid lubricant loss or morphological surface damage. Therefore, there is a need to continuously develop surface treatment methods and treated surfaces that can repel liquids and maintain their repellency for a long time. Summary of the invention
[0005] The present disclosure provides a method in one embodiment, the method comprising: providing a substrate having a surface, wherein the surface is hydroxylated; and exposing the hydroxylated surface of the substrate to a PDMS oligomer. The PDMS oligomer has the formula:
[0006] R1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-R2
[0007] Wherein at least one of R1 or R2 comprises: -(CH2) m -R3, R3 is -Cl, -O-(CH2) x H, -SiCl3 or -Si(O-(CH2) x H) is one of R3, x is an integer in the range of 0 to 10, m is an integer in the range of 0 to 10, and n is an integer in the range of 10 to 500. R3 in the PDMS oligomer undergoes hydrolysis, so that one terminal Si atom in the PDMS oligomer is covalently bonded to the hydroxylated surface through a condensation reaction to form a PDMS polymer grafted layer on the surface.
[0008] Another embodiment of the present disclosure is an article comprising a substrate having a surface with a PDMS polymer grafted layer on the surface, wherein each PDMS polymer has the formula:
[0009] -Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-Q2
[0010] Where Q1 is -O- or -O-(CH2) m -O-, Q2 is -(-Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-) p -Q3, Q3 is -OH, -(CH2) m -OH, -Si(OH)3 or -(CH2) m -Si(OH)3, m is an integer in the range of 0 to 10, n is an integer in the range of 10 to 500, p is an integer in the range of 0 to 500, and Q1 is the terminal end of the PDMS polymer covalently bonded to the surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] For a more complete understanding of the present disclosure, reference is now made to the following detailed description in conjunction with the accompanying drawings. Reference is now made to the following description in conjunction with the accompanying drawings, in which:
[0012] Figure 1 A flowchart showing an example method embodiment of the present disclosure;
[0013] Figure 2 A conceptual schematic diagram showing an embodiment of an article of manufacture of the present disclosure;
[0014] Figure 3A Schematic diagram showing the one-step autocatalytic grafting of chlorine-terminated PDMS polymer onto hydroxylated substrates;
[0015] Figure 3B Schematic diagram showing a droplet sliding on a sloping semi-liquid surface (SLS);
[0016] Figure 3C Atomic force microscopy (AFM) images showing glass surfaces coated with small molecule chlorosilanes;
[0017] Figure 3D AFM images showing flexible PDMS polymer grafted glass SLS;
[0018] Figure 3E Time-series images showing the liquid repellency of 2μL Krytox101 and 20μL water on a glass substrate with a tilt angle of 10° and a bare glass SLS;
[0019] Figure 3F A comparison of the contact angle hysteresis (CAH) versus heating time at 105°C for a silicon substrate SLS and a semi-liquid infused surface (SLIPS) made of black silicon infused with Krytox101, with the inset showing that after 3 minutes, a 5 μL water droplet was fixed on SLIPS due to lubricant evaporation, but was still movable on SLS after more than 3 months;
[0020] Figure 3G 3G UV / Vis spectra of SLS on glass and bare glass are shown, which demonstrate the optical transparency of SLS;
[0021] Figure 4A Attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy and synthesis optimization showing the chemical composition of grafted PDMS polymers used to fabricate SLS;
[0022] Figure 4B Scanning electron microscope (SEM) image showing a cross-sectional view of SLS on silicon with a grafting time of 60 minutes and a grafting temperature of 60°C;
[0023] Figure 4C Shows the relationship between the contact angle (CA) and CAH of the water droplet in SLS and the grafting temperature within a grafting time of 60 min. The dashed line indicates that the water CAH is 5°;
[0024] Figure 4D The relationship between the corresponding thickness of SLS measured by ellipsometry and the grafting temperature is shown, and the inset shows the contact angle of a water drop on SLS;
[0025] Figure 4E The relationship between the CA and CAH of the water droplet in SLS and the grafting temperature during the grafting time of 60 min is shown. The dashed line indicates that the water CAH is 5°;
[0026] Figure 4F The relationship between the corresponding thickness of SLS measured by ellipsometry and the grafting temperature is shown, and the inset shows the contact angle of a water drop on SLS;
[0027] Figure 5A Shows the CA of water on different substrates before and after SLS coating;
[0028] Figure 5B Shows the CAH of toluene on SLS coatings of different substrates;
[0029] Figure 5C The CA and CAH of different liquids on the silicon SLS coating are shown;
[0030] Figure 5DThe temperature-dependent sliding velocity of 5 μL hexadecane on a silicon substrate SLS and SLIPS (anodized aluminum oxide AAO, infused with Krytox101) at a tilt angle of 3° is shown.
[0031] Figure 5E The time-lapse images show a 1 μL fluorocarbon droplet (FC72) and a 5 μL crude oil and mineral oil droplet sliding down the SLS at a 10° tilt angle, and the scale bar is 1 mm;
[0032] Fig. 5F The liquid repellency of SLS-coated silicon relative to bare silicon toward crude oil, mineral oil, and urine is shown;
[0033] Figure 5G The liquid repellency of SLS coated aluminum foil against crude oil, mineral oil, and urine is shown relative to bare aluminum foil;
[0034] Fig. 6A Shows the durability of liquid repellency of SLS and SLIPS (black silicon infused with Krytox 101) on silicon after continuous abrasion testing with tissue paper: Water CAH, and the inset shows the abrasion test protocol;
[0035] Figure 6B Shows the persistence of liquid repellency of SLS and SLIPS (black silicon infused with Krytox 101) on silicon after successive bonding tests using tape: water CAH, and the inset shows the bonding test scheme;
[0036] Figure 6C Photographs showing the abrasion test protocol;
[0037] Fig.6D Photographs showing bonding test protocols;
[0038] Fig. 6E The displayed photos show the repellency of SLS to water and hexadecane after 1000 cycles of abrasion testing;
[0039] Fig. 6F The displayed photos show the repellency of SLS to water and hexadecane after 1000 cycles of bonding tests;
[0040] Figure 6G The photos shown show the liquid repellency of SLS to water and mineral oil after scratch damage;
[0041] Fig. 7A Schematic diagram showing PTFE-coated hydrophobic surface (HPS), SLS, and SLIPS;
[0042] Figure 7B The photos shown compare the fog capture of HPS, SLS, and SLIPS surfaces from 0 to 20 minutes;
[0043] Figure 7C The photos shown compare the persistent fog capture of HPS, SLS, and SLIPS surfaces over a period of 253 minutes;
[0044] Fig.7D Comparison of fog capture rates of HPS, SLS, and SLIPS is shown and the inset shows the water CA of different surfaces before and after the fog capture test;
[0045] Fig. 7E The different situations of average droplet shedding radius and shedding frequency of HPS, SLS and SLIPS during fog capture from 0 to 20 minutes are shown, and the inset shows the photos of shedding water droplets on the three surfaces for size comparison;
[0046] Figure 7F The displayed photographs illustrate the self-cleaning ability of glass SLS on iron oxide particles, where the water CA is 104.9° and the substrate tilt angle is 30°;
[0047] Figure 7G Photo captions of the exhibit are provided by Self-cleaning ability of superhydrophobic surface (SHS) made of commercial coating on iron oxide particles with water CA of 152.3° and substrate tilt angle of 30°;
[0048] Figure 8 Schematic diagram showing the preparation of SLS using the gas phase in a vacuum oven;
[0049] Fig. 9A AFM images showing the silicon surface before and after PDMS grafting;
[0050] Fig. 9B Other AFM images showing the silicon surface before and after PDMS grafting;
[0051] Fig. 9C SEM images showing cross-sectional views of silicon before and after PDMS grafting;
[0052] Fig. 10A Shows the sliding angle (SA) of a 5 μL water droplet on a silicon SLS coating using a 60 min coating time and different coating temperatures;
[0053] Fig. 10B shows the SA of a 5 μL water droplet on a silicon SLS coating using a 60 °C coating temperature and different coating times;
[0054] Fig.11 Schematic diagram showing the possible effect of temperature on the evaporation of liquid Cl-PDMS-Cl in a vacuum oven is presented;
[0055] Fig. 12ACross-sectional images showing water (5 μL) CA on glass substrate before and after PDMS coating;
[0056] Fig. 12B Cross-sectional images showing water (5 μL) CA on silicon substrate before and after PDMS coating;
[0057] Fig. 12C Cross-sectional images showing CA of water (5 μL) on Ti substrate before and after PDMS coating;
[0058] Fig.12D Cross-sectional images showing water (5 μL) CA on Fe substrate before and after PDMS coating;
[0059] Fig.12E Cross-sectional images showing CA of water (5 μL) on Cr substrate before and after PDMS coating;
[0060] Fig.12F Cross-sectional images showing CA of water (5 μL) on Ni substrate before and after PDMS coating;
[0061] Figure 12G Cross-sectional images showing CA of water (5 μL) on Al substrate before and after PDMS coating;
[0062] Fig.13A Shows the cross-sectional images of water, toluene, and acetone (5 μL) sliding down the silicon SLS coating at a tilt angle of 10°, where the scale bar is 1 mm;
[0063] Fig. 13B Shows the comparison of different types of liquids (5 μL) sliding down a silicon SLS coating at a 10° tilt angle;
[0064] Fig.14 To show the comparison of water CAH on SLS coatings of different metal substrates;
[0065] Fig.15A Shows cross-sectional images of a hexadecane droplet sliding on a silicon SLS coating at different temperatures;
[0066] Fig. 15B Shows cross-sectional images of a hexadecane droplet sliding on SLIPS (Krytox 101-infused AAO surface) at different temperatures;
[0067] Fig.16A A schematic diagram showing a high temperature aging test performed by heating at 105°C;
[0068] Fig. 16B Photographs showing high temperature aging tests conducted by heating at 105°C;
[0069] Fig. 16C The photos shown show the liquid repellency of SLS to water and hexadecane after aging at high temperature for more than 3 months;
[0070] Fig.17A Images shown show SLIPS surfaces (black silicon infused with Krytox 101) before and after harsh durability tests of high temperature aging, abrasion, and adhesion at different durations;
[0071] Fig. 17B The images presented show the SLS surface (PDMS grafted silicon) before and after harsh durability tests of high temperature aging, abrasion, and adhesion at different durations;
[0072] Fig.18 Shows the CAH of water on PTFE-coated hydrophobic surfaces (HPS), SLS, and SLIPS before and after a 260-minute fog capture test;
[0073] Fig.19A Schematic diagram showing the structure of transparent SLIPS made by spin-coating an organogel onto a glass slide and then infusing with silicone oil;
[0074] Fig.19B The displayed photographs illustrate the self-cleaning ability of glass SLIPS on iron oxide particles with a water CA of 108.5° and a substrate tilt angle of 30°;
[0075] Fig.19C The displayed photographs illustrate the self-cleaning ability of bare glass on iron oxide particles, where the water CA is 33.0° and the substrate tilt angle is 30°;
[0076] Fig.19D Schematic diagram showing the scheme for a superhydrophobic surface before being contaminated by pollutant particles;
[0077] Fig.19E Schematic diagram showing the scheme for a superhydrophobic surface after contamination, where contaminant particles enter the microstructure on the surface, inducing air lubricant loss;
[0078] Fig.19F Schematic diagram showing the scheme for injecting liquid into a surface prior to contamination;
[0079] Figure 19G A schematic diagram showing a scheme for injecting a liquid into a surface after contamination, wherein a liquid envelope is formed on the contaminant;
[0080] Fig. 20Shows the relationship between ice adhesion strength, water CAH, PDMS oligomer molecular weight and viscosity on SLS grafted on an example glass substrate embodiment of the present disclosure;
[0081] Fig.21 shows the relationship between water CAH, PDMS oligomer molecular weight and viscosity on SLS grafted on an example aluminum substrate embodiment of the present disclosure; and
[0082] Fig. 22 The bond strength of SLS grafted using a semi-liquid solvent mixture containing different ratios of PDMS and an inert liquid on an example glass substrate embodiment of the present disclosure is demonstrated. DETAILED DESCRIPTION
[0083] As part of the present disclosure, we have developed a surface treatment method that includes treating a substrate surface with certain PDMS oligomers as disclosed herein, wherein the resulting treated surface has a PDMS polymer grafted layer covalently bonded thereto. As further disclosed herein, the surface treatment method can be applied to a wide range of different types of article substrates, and the treated surface can repel a wide range of liquids (e.g., liquids with different surface tensions and polarities). In addition, as further described herein, at least some embodiments of the treated surface can maintain its repellency even after the surface treatment.
[0084] We have discovered that the termini of the PDMS oligomers of the present disclosure can be covalently bonded to a hydroxylated substrate surface by a simple one-step condensation reaction, thereby covalently tethering the PDMS oligomer to the substrate surface or covalently tethering to other PDMS oligomers to form covalently linked chains of such PDMS oligomers, such that the PDMS polymer is covalently tethered to the surface, thereby forming a grafted layer.
[0085] Although the scope of the present disclosure is not limited by theory, we believe that the surface treatment methods and formation of the grafted layer we disclose result in single ends of individual PDMS polymers being covalently bonded to the substrate surface. We further believe that such single-point-attached PDMS polymer molecules have a high degree of rotational flexibility, which can impart to the grafted layer liquid-like or semi-liquid surface (SLS)-like properties that we believe can promote liquid repellency.
[0086] Surprisingly, our surface treatment method is effective, given that some reports have suggested that surface treatment methods using low molecular weight chlorosilanes (e.g., molecular weight MW≤about 2kD) are not effective in producing durable liquid-repellent surfaces, and other reports have suggested that surface treatment methods using high molecular weight PDMS polymers (e.g., MW≥about 100kD) can produce treated surfaces with kinks between PDMS polymer chains, resulting in limited liquid repellency of the treated surface. In addition, although the scope of the present disclosure is not limited by theory, we believe that surfaces treated with such low molecular weight chlorosilanes or such high molecular weight PDMS polymers are unlikely or unreliable to produce a grafted layer with semi-liquid surface (SLS)-like properties (e.g., disclosed herein).
[0087] However, some embodiments of the methods and articles produced using the same can produce useful SLS-like properties when using PDMS oligomers with MW < 2 kD (e.g., about 0.5 or about 1 kD) or > 100 kD (e.g., up to about 140 kD). For example, when using PDMS oligomers with MW < 2 kD, SLS coverage on the substrate may not be complete. For example, when using PDMS oligomers with MW > 100 kD, kinks may occur.
[0088] One embodiment of the present disclosure is a method.
[0089] Figure 1 A flowchart of an example method 100 embodiment of the present disclosure is shown. Figure 1 , an embodiment of method 100 may include providing a substrate having a surface, wherein the surface is hydroxylated (step 105). Embodiments of the method may also include exposing the hydroxylated surface of the substrate to a PDMS oligomer (step 110).
[0090] An example of a PDMS oligomer has the formula:
[0091] R1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-R2
[0092] Wherein at least one of R1 or R2 comprises: -(CH2) m -R3, and R3 is -Cl, -O-(CH2) x H, -SiCl3 or -Si(O-(CH2) xIn step 115, the PDMS oligomer is covalently bonded to an oxygen atom of the surface, or the terminal oxygen atom of the PDMS oligomer is covalently bonded to another atom of the substrate, such as a Si atom of a silicon substrate.
[0093] The R3 group in the above formula has a functional group that can participate in the condensation reaction, and the type of the functional group can have a variety of structural formulas, depending on the value of x. For example, when x=0, then R3 can be one of -Cl, -OH, -SiCl3 or -Si(OH)3; when x=1, then R3 can be one of -Cl, -O-CH3, -SiCl3 or -Si(O-CH3)3; or when x=2, then R3 can be one of -Cl, -O-CH2-CH3, -SiCl3 or -Si(O-CH2-CH3)3.
[0094] R1 or R2 in the above formula can have a variety of forms, depending on the value of m, which sets the length of the optional alkyl chain located at the end covalently tethered to the surface and between the repeating units of the PDMS oligomer covalently linked in series with each other. For example, when m=0, then one or both of R1 or R2 can be -R3; when m=1, then one or both of R1 or R2 can be -(CH2)2-R3; or when m=2, then one or both of R1 or R2 can be -(CH2)2-R3, wherein R3 has any of the above structural formulas.
[0095] The value of n sets the chain length of the individual PDMS oligomers by specifying the number of dimethylsiloxane repeating units of (O-Si(CH3)2-). In some embodiments, when n is less than 10, then the resulting PDMS polymer covalently tethered to the surface may not have semi-liquid surface (SLS)-like properties that promote liquid repellency to a desired level, even if multiple PDMS oligomers are covalently linked to form the PDMS oligomer chain. In some embodiments, when n is greater than 500, then the resulting adjacent PDMS polymer covalently tethered to the surface may have a length long enough to cause a kink between adjacent polymers, resulting in less than a desired level of liquid repellency. In some embodiments, it is advantageous when n is a value in the range of 20 to 100.
[0096] When either R1 or R2 includes R3, then R3 at the end of the PDMS oligomer that is not tethered to the surface can undergo further condensation reactions as part of step 115. That is, R3 can hydrolyze to form a covalent bond with another PDMS oligomer, and so on, to produce a series of covalently linked chains of PDMS oligomers, thereby producing a PDMS polymer.
[0097] In some embodiments, both R1 and R2 may have the same one of R3. For example, both ends of a PDMS oligomer having R1 and R2 at either end may include a -Cl functional group or an -OH functional group as R3. In other embodiments, R1 and R2 may have different one of R3. For example, one end of a PDMS oligomer having R1 may have a -Cl functional group as R3, and the opposite end of a PDMS oligomer having R2 may have a -OH functional group as R3.
[0098] When only one R1 or R2 includes R3, then the condensation reaction of R3 covalently tethers one end of the PDMS oligomer to the surface as part of step 115, but the other PDMS oligomer is not further covalently attached to the surface-tethered PDMS oligomer. For example, in some embodiments, one of R1 or R2 has -(CH2) m -R3, and the other of R1 or R2 comprises -(CH2) o CH3, wherein o is an integer in the range of 0 to 10. In such embodiments, the end of the PDMS oligomer not tethered to the surface is terminated with an alkyl group (e.g., when o = 0, 1 or 2, the other of R1 or R2 not tethered to the surface is -CH3, -(CH2)1CH3, -(CH2)2CH3, respectively).
[0099] Non-limiting examples of substrates (e.g., provided as part of step 105) include silicon, glass, cross-linked PDMS organogel, plastic, Al, Ti, Fe, Ni or Cr metal substrates, or multilayer combinations thereof. For example, in some embodiments, the glass, plastic, silicon or metal substrate can be coated with a Ti layer, and the Ti layer can be a hydroxylated surface.
[0100] In some embodiments, as part of step 110, the hydroxylated surface of the substrate is exposed to the PDMS oligomer for a period of time sufficient to allow complete condensation of all hydroxyl groups on the surface to occur. For example, in some embodiments, the period of time for exposure (step 110) is in the range of 5 to 720 minutes, or in the range of 10 to 60 minutes. For example, in some embodiments, for PDMS oligomers of lower molecular weight (e.g., about 0.5 to about 2 kD), the period of time for exposure (step 110) can be less than 5 minutes. For example, in some embodiments using a substrate surface that has not been surface treated, the period of time for exposure (step 110) can be in the range of 720 to 1440 minutes.
[0101] In some embodiments, to facilitate control of the environment to which the hydroxylated surface of the substrate is exposed, the exposing step 110 can be performed inside a container in which the substrate is placed. For example, in some such embodiments, the container can be a sealed chamber, wherein the temperature and pressure inside the chamber can be controlled, for example, to promote the completion of the condensation reaction, maintain the hydroxylated surface until the condensation reaction is complete, maintain the PDMS oligomer at a desired concentration or phase, or facilitate the inclusion of other materials into the container.
[0102] For example, in some such embodiments, the PDMS oligomer in the container can be in a gas phase.
[0103] For example, in some such embodiments, in order to control the reaction rate or maintain the PDMS in a gas phase, the container may be configured to maintain a temperature value inside the container within a range of 20 to 100° C. or within a range of 40 to 60° C.
[0104] For example, in some such embodiments, in order to maintain the water humidity in the container at a low level during the ongoing condensation reaction (the condensation reaction can produce water as a byproduct and thereby slow down or reverse the condensation reaction), the container can be configured to maintain the reduced pressure inside the container in the range of 0.1 to 0.9 Torr or in the range of 0.1 to 0.2 Torr. For example, in some embodiments, the water humidity in the container is 20%, 10%, or 1% or less.
[0105] For example, in some such embodiments, the PDMS oligomer in the gas phase has a concentration of about 100% by volume in the container. However, in some embodiments, in order to reduce the concentration of the gas phase PDMS oligomer in the container, the container may further include a gas (eg, an inert gas).
[0106] However, in other embodiments, the PDMS oligomer may be in a liquid phase and the exposure step 110 may not be performed inside a container, but in some embodiments, a container containing a substrate and a liquid phase PDMS oligomer may still be used. In some embodiments, the use of a PDMS oligomer in a liquid phase for the exposure step 110 may be advantageous, such as when processing highly porous or rough substrate surfaces (e.g., substrate surfaces having a surface roughness greater than 1 nm or, in some embodiments, a surface roughness of at least about 10 nm, 100 nm, or 1000 nm before forming a graft layer thereon).
[0107] For example, in some such embodiments where a container is not used, a liquid phase PDMS oligomer may be deposited (e.g., via spraying) onto a substrate surface. In any such embodiments where a container is present or absent, it may be advantageous to maintain the temperature of the liquid phase PDMS oligomer at a value in the range of 20 to 100° C. or 40 to 60° C. In any such embodiments, it may be advantageous to have the liquid phase PDMS oligomer have a low water content (e.g., 1 wt % or less water in some embodiments). In any such embodiments, the PDMS oligomer in liquid phase may have a concentration of about 100% by volume, and in some embodiments, in order to reduce the PDMS oligomer concentration, the liquid PDMS oligomer may be mixed with another liquid (e.g., an inert liquid) to form a diluted PDMS oligomer solution.
[0108] The inclusion of an inert liquid can advantageously: (1) reduce the material cost of the PDMS oligomer, which is typically more expensive than the inert liquid; (2) reduce viscosity, especially when using a high molecular weight PDMS oligomer (e.g., MW = 100 kD to 140 kD); and (3) facilitate removal via evaporation after application of the liquid phase PDMS. In some embodiments, the inert liquid can be or include ethanol or heptane or a similar inert liquid, such as other inert liquids, such as other alcohols or hydrocarbons. In some embodiments, the volume percentage (vol%) of PDMS can be a value in the range of 100 to 5 vol%, and the remainder can be the inert liquid.
[0109] In some embodiments, neither R1 nor R2 includes R3 which is a -Cl functional group. In such embodiments, the acid is not automatically generated as part of the condensation reaction, and therefore the condensation reaction does not proceed. In such embodiments, it is advantageous to add the acid to the gaseous or liquid PDMS oligomer. For example, in some embodiments, when the PDMS oligomer is present in a container and is in a gas phase, it is advantageous to further include an acid vapor (e.g., gaseous hydrochloric acid, sulfuric acid, nitric acid, or a combination thereof) in the container. For example, in some embodiments, when the PDMS oligomer is in a liquid phase, it is advantageous to include an acid (e.g., hydrochloric acid, sulfuric acid, nitric acid, or a combination thereof) in the liquid PDMS oligomer to form an acidified PDMS oligomer solution.
[0110] like Figure 1 As described in , some embodiments of method 100 may further include forming a hydroxylated surface on the substrate surface (step 120). For example, in some such embodiments, forming the hydroxylated surface on the substrate surface may include exposing the substrate surface to an oxygen plasma treatment, a corona treatment, a strong oxidizing solution, or a combination thereof. For example, in some embodiments, exposing the substrate surface to the oxygen plasma treatment may include applying a plasma power setting in the range of about 20 to 300 W or in the range of about 190 to 210 W, an O2 pressure in the range of about 50 to 300 mTorr, or in the range of about 180 to 220 mTorr, for a treatment period in the range of about 0.5 to 30 minutes or in the range of about 15 to 25 minutes. For example, in some embodiments, exposing the substrate surface to the corona treatment may include applying a power setting in the range of about 20 to 300 W and a treatment duration in the range of about 0.5 to 30 minutes. For example, in some embodiments, exposing the substrate surface to a strong oxidizing solution may include exposure to a mixture of sulfuric acid and hydrogen peroxide (eg, Piranha solution) with an exposure duration ranging from about 0.5 to 30 minutes.
[0111] However, in other embodiments, no additional step of forming a hydroxylated surface on the substrate surface is required. For example, oxygen plasma treatment or other surface treatment may not be applied. For example, when there is an oxide layer on the substrate surface (e.g., silicon, glass, metal), hydroxyl groups may be inherently or naturally formed in the air. To our surprise, in such cases, no surface treatment is required. However, we found that after a longer reaction time (e.g., the reaction time of step 110 is in the range of 6 hours to 12 hours or 12 to 24 hours), PDMS oligomers (e.g., single-branch PDMS) can be grafted on the surface and the surface exhibits properties as good as SLS formed on a plasma surface treated substrate. Therefore, according to steps 110 and 115, increasing the liquid phase reaction time or reaction temperature can promote PDMS oligomer grafting, while step 120 cannot.
[0112] In some embodiments, to further enhance liquid repellency, the method may further include adding liquid PDMS molecules onto the surface through a PDMS polymer grafted layer on the surface (step 125). Non-limiting examples of such liquid PDMS molecules include: Cl-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2-Cl(n=10 to 500), OH-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2-OH(n=10 to 500), CH3O-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2-OCH3(n=10 to 500), H(CH2)2O-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2-O(CH2)2H(n=10 to 200), Cl3Si-O-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2-O-SiCl3(n=10 to 200), (OH)3Si-O-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2-O-Si(OH)3(n=10 to 200), (CH3O)3Si-O-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2-O-Si(OCH3)3(n=10 to 200), (H(CH2)2O)3Si-O-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2-O-Si-(O(CH2)2H)3(n=10 to 200), Cl-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)3(n=10 to 200), OH-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)3(n=10 to 200), CH3O-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)3(n=10 to 200), H(CH2)2O-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)3(n=10 to 200), Cl3Si-O-Si(CH3)2-O-(Si(CH3)2O) n-Si(CH3)3 (n = 10 to 200), (OH)3Si - O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)3 (n = 10 to 200), (CH3O)3Si - O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)3 (n = 10 to 200), (H(CH2)2O)3Si - O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)3 (n = 10 to 200), Cl - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), OH - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), CH3O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), H(CH2)2O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), Cl3Si - O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (OH)3Si - O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (CH3O)3Si - O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (H(CH2)2O)3Si - O - Si(CH3)2 - O - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), ClSi(CH3)2 - (CH2)2 - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), OHSi(CH3)2 - (CH2)2 - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), CH3OSi(CH3)2 - (CH2)2 - (Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), H(CH2)2OSi(CH3)2 - (CH2)2 - (Si(CH3)2O) n-Si(CH3)2OH (n = 10 to 200), Cl3Si-(CH2)2-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (OH)3Si-(CH2)2-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (CH3O)3Si-(CH2)2-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (H(CH2)2O)3Si-(CH2)2-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), ClSi(CH3)2-(CH2)2-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), OHSi(CH3)2-(CH2)2-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), CH3OSi(CH3)2-(CH2)2-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), H(CH2)2OSi(CH3)2-(CH2)2-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), Cl3Si-(CH2)2-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (OH)3Si-(CH2)2-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (CH3O)3Si-(CH2)2-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), (H(CH2)2O)3Si-(CH2)2-Si(CH3)2-O-(Si(CH3)2O) n -Si(CH3)2OH (n = 10 to 200), or a mixture thereof.
[0113] In some embodiments, after the hydrolysis step 115, the method further comprises a step 130 of rinsing off the PDMS oligomers that are not grafted onto the surface. For example, the free PDMS oligomers may be sprayed or immersed with a bath of toluene, acetone, or a combination thereof as part of step 130. However, in other embodiments, in addition to or as an alternative to adding liquid PDMS molecules onto the surface in step 125, some or all of the unreacted free PDMS oligomers may be left on the surface, for example, to further enhance liquid or ice repellency.
[0114] Another embodiment of the present disclosure is an article of manufacture. Figure 2 A schematic diagram of one embodiment of an article 200 of the present disclosure is shown. Figure 2 , an embodiment of the article includes a substrate having a surface (e.g., substrate 205, surface 210) having a PDMS polymer grafted layer (e.g., grafted layer 215, PDMS polymer 220) on the surface. Various PDMS polymers have the formula:
[0115] Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-Q2
[0116] Where Q1 is -O- or -O-(CH2) m -O-; Q2 is -(-Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-) p -Q3, Q3 is -OH, -(CH2) m -OH, -Si(OH)3 or -(CH2) m -Si(OH)3, m is an integer in the range of 0 to 10, n is an integer in the range of 0 to 500, and p is an integer in the range of 0 to 500, and Q1 is an end of a PDMS polymer covalently bonded or tethered to the surface (e.g., tethered end 225).
[0117] m and n are similar to those described above. Q2 includes additional PDMS oligomer repeating units (p) that are covalently linked to the PDMS oligomer covalently tethered to the surface and to each other in series; and Q3 is the untethered opposite end of the PDMS polymer (e.g., untethered end 230). For example, when p=0, there are no additional PDMS oligomer repeating units and the PDMS polymer is Q1-Si(CH3)2-(O-Si(CH3)2-) n-O-Si(CH3)2-Q3; when p=1, there is an additional PDMS oligomer repeat unit and the PDMS polymer is Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-(-Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-)-Q3; when p=2, there are two additional PDMS oligomer repeating units and the PDMS polymer is Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-(-Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-)2-Q3.
[0118] In some embodiments of the article, the PDMS polymer grafted layer has an average thickness (eg, thickness 235 ) in the range of about 10 nm to 40 nm, and in some embodiments, in the range of 25 nm to 35 nm.
[0119] In some embodiments of the article, the surface having the PDMS polymer grafted layer thereon has a surface roughness of 1 nm or less.
[0120] In some embodiments of the article, the PDMS polymer grafted layer is a liquid repellent surface. For example, in some embodiments, a water drop on a surface having a PDMS polymer grafted layer thereon has a contact angle hysteresis in the range of 0 to 5 degrees, and in some embodiments, in the range of 0.5 to 1.5 degrees.
[0121] In some embodiments of the article, the article may further include liquid PDMS molecules (eg, liquid PDMS 240 ), including any of the liquid PDMS molecules disclosed in the context of step 125 , on the surface having the PDMS polymer grafted layer thereon.
[0122] like Figure 2As described in , the PDMS polymer chains can have a brush-like structural appearance of the substrate, wherein the individually linked PDMS polymer molecules are covalently attached to the surface (e.g., at the tethered end 225). Although the scope of the present disclosure is not limited by theoretical considerations, it is believed that such PDMS chains in the semi-liquid coating are therefore not physically tangled or chemically cross-linked with each other, or the physical tangling and / or chemical cross-linking that occurs is at least reduced. As a result, the PDMS molecular chains are able to maintain their high dynamic flexibility, which helps to provide liquid-like lubrication. Therefore, the SLS coating can exhibit better repellency to liquids including water, organic liquids, and oils than a cross-linked solid PDMS coating, and exhibit lower ice bonding strength than such a cross-linked solid PDMS coating.
[0123] In any such embodiments of the article, the surface having a PDMS polymer grafted layer thereon can be part of a pipe, a land, air or water transport vehicle, a window, a window cleaning blade, a wind turbine blade, a heat transfer device, or an article of clothing (e.g., a shoe, jacket or hat).
[0124] Embodiments of the methods and articles are disclosed herein in the context of a substrate surface exposed to a single chemical formula type of PDMS oligomer to form a grafted layer of a single chemical formula type of PDMS polymer on the surface. However, any embodiments of the methods and articles may include exposing a substrate surface to a plurality of different chemical formula types of PDMS oligomers to form a grafted layer of a plurality of different chemical formula types of PDMS polymers on the surface.
[0125] Experimental Results
[0126] The disclosed example methods and article embodiments are presented to demonstrate our one-step condensation reaction method to form a durable amphiphobic grafted layer (e.g., with a semi-liquid surface (SLS)). As disclosed herein, such grafted layers and surfaces can be made by tethering one end of a liquid polymer chain of a polydimethylsiloxane (PDMS) oligomer to a solid substrate, but keeping the other end mobile. The molecularly patterned mobile polymer chains completely cover the solid substrate. Unlike lubricants that are physically retained on a liquid-injected surface, the mobile polymer chains chemically bond to the solid surface to form an SLS. The tethered PDMS polymer has a high molecular weight due to its unkinked polymer dynamics and extremely low glass transition temperature (T g =-125°C) while maintaining a higher molecular mobility.
[28] Although tethered liquid polymers cannot behave like real liquids, unkinked polymer brushes with a mobile molecular chain at one end still show liquid-like lubrication in terms of droplet repellency.
[42] Such semi-liquid surfaces do not rely on solid textures to retain air or liquid lubricants that repel water and low surface tension fluids. In fact, chemically bonded mobile molecular chains can maintain lubricity in harsh environments of long-term operation. We demonstrate that SLS maintains excellent liquid repellency after heating at 105°C for more than three months, 1000 cycles of wear and adhesion tests, and scratch tests. In addition, SLS can be created on different plasma-treated substrates that are covered with oxide layers such as silicon, glass, and metals (such as Ti, Fe, Ni, Cr, and Al) while maintaining optical transparency. We demonstrate that our SLS outperforms other types of liquid-repellent surfaces, such as liquid-injected surfaces and superhydrophobic surfaces (SHS), in terms of persistence, fog capture, self-cleaning, and repellency of complex fluids (such as urine) and extremely low surface tension fluids (such as FC72 and Krytox101).
[0127] We disclose certain embodiments of our method that do not require solvents, catalysts, or specific conditions to produce SLS. Figure 3A As shown in , a chlorine-terminated PDMS (Cl-PDMS-Cl) oligomer with a viscosity of 20-50 cSt (Gelest Inc., molecular weight of 2000-4000) is used in the gas phase grafting method. Hydrolysis and polycondensation occur simultaneously in this one-step surface grafting. In short, when moisture is present, Cl-PDMS-Cl spontaneously hydrolyzes due to its high reactivity to water molecule nucleophiles to form hydroxyl-terminated PDMS (OH-PDMS-OH). Then, the hydrochloric acid produced by the hydrolysis of Cl-PDMS-Cl causes the PDMS polymer chains to undergo rapid covalent grafting and reactive growth through autocatalytic polycondensation.
[43] In this paper, Cl-PDMS-Cl oligomers were selected for grafting modification because both ends of the molecule contain reactive chlorine groups. Therefore, the length of the PDMS polymer can grow rapidly starting from the serial covalently linked PDMS oligomers. In addition, the PDMS polymer with movable chains has a high degree of flexibility due to its low rotation barrier of repeated Si-O-Si bonds (bond angle = 143°).
[28] The flexible grafted PDMS polymer, which is movable at one end and tethered at the other end, behaves like a semi-liquid and can maintain its high mobility through rotational and / or bending activities.
[33] Compared with previously reported work, the high molecular mobility enables SLS to have unprecedented liquid repellency for both water and organic liquids ( Figure 3B and Table S1 ).
[0128] Different reaction systems (with or without the addition of solvent and catalyst) and various reaction conditions were studied to obtain the SLS preparation parameters (Tables S2, S3).
[0129] We demonstrate that the best SLS performance can be achieved using Cl-PDMS-Cl in either the gas or liquid phase under reduced pressure. In this work, all semi-liquid surfaces were prepared in a vacuum oven at 60 °C for 60 min in the gas phase unless otherwise stated ( Figure 8 Atomic force microscopy (AFM) images show that the roughness of SLS is reduced (0.35nm) compared to the surface coated with small molecule trimethylsilyl chloride (Me3SiCl) (2.26nm) or the bare glass surface (2.72nm) ( Figure 3C , 3D and Figures 9A to 9C The subnanometer roughness of SLS indicates that the semi-liquid surface grafted with flexible PDMS polymer has an extremely smooth surface. Such liquid-like SLS can repel both low and high surface tension liquids (liquid surface tension γ), such as water (γ = 72.8 mN m -1 ), and even repelling fluorocarbon liquid Krytox101 (γ=17mN m -1 ) and FC72 (γ=10mN m -1 )( Figure 3E , Table S4 ).
[0130] Since FC72 evaporates quickly, Figure 3E Only Krytox101 is shown. The repellency of SLS to FC72 is demonstrated by the magnified side view taken by the camera mounted on the goniometer. Many liquids showed very low contact angle hysteresis (CAHΔθ≤1.0°, Table S4). CAHΔθ is the advancing contact angle (θ adv ) and the receding contact angle (θ rec ) (Δθ=θ adv -θ rec The small CAHΔθ of the droplets indicates that SLS has good liquid repellency. In addition, the thermal stability of SLS is high due to the strong Si-O bond dissociation energy between PDMS molecules and the substrate (444 kJ / mol).
[28] SLS shows ultralow CAH (Δθ ≤ 1.5°) for water even after heating at 105 °C for more than 3 months, while SLIPS loses water repellency after only 3 minutes due to strong lubricant evaporation at such high temperatures ( Figure 3F ). In addition, PDMS has inherent optical transparency. SLS shows the same optical transparency as bare glass substrate ( Figure 3G). This liquid-repelling polymer coating does not affect the light transmittance of the substrate. Although both SLS and SLIPS show excellent liquid repellency and optical transparency, the liquid-like polymer is chemically bonded to SLS, while the liquid lubricant is physically retained on SLIPS. SLS maintains lubricity under harsh conditions (such as high temperature) and outperforms SLIPS in long-term operation.
[0131] The chemical composition of SLS was analyzed by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR). Figure 4A As shown, SLS is located at 2965cm -1 (νC-H), 1261cm -1 (νSi-CH3), 1039 / 1097cm -1 (νSi-O-Si), 806cm -1 The characteristic peak of (νSi-(CH3)2) indicates that the PDMS polymer has been successfully grafted. [44,45] Compared with bare silicon and plasma-treated silicon, SLS showed a -1 and 3000-3650cm -1 The enhanced absorption peaks corresponding to the vibration of Si-OH and OH in the adsorbed water molecules ( Figure 4A ). [44,45] like Figure 2 As shown in , the PDMS polymer on SLS is terminated with hydroxyl groups, which can facilitate the rapid nucleation of water molecules. [5] Scanning electron microscopy (SEM) images also confirmed the presence of a PDMS grafted layer on the SLS, with a thickness of about 30 nm ( Figure 4B and Figures 9A to 9C ). To better understand the PDMS grafting kinetics, we investigated the effects of reaction temperature and reaction time on the wettability and mobility of droplets on SLS. All semi-liquid surfaces were prepared on silicon by vapor phase grafting in a vacuum oven. When the coating temperature was increased to about 50 °C for 60 min, the CAH and sliding angle (SA) of the water droplet on SLS showed a sharp decay ( Figure 4C and Fig. 10A ). Specifically, SLS with a coating temperature below 50°C showed large CAH (Δθ>12°) and SA (>58°) for water. When the coating temperature increased to more than 60°C, ultra-low water CAH (Δθ=1.0°) and SA (=4°) were obtained ( Figure 4C and Fig. 10A The reason is that the PDMS polymer grafted at 60°C (thickness = 30.1 nm) is thicker and denser than the 4.8 nm PDMS polymer grafted at 20°C ( Figure 4D). At 20 °C, the thinner PDMS coating indicates that the PDMS layer is less dense. The elevated temperature can significantly enhance the evaporation of the liquid Cl-PDMS-Cl, thereby inducing a high interfacial concentration of the reactants and rapid hydrolysis and polycondensation ( Fig.11 ). Therefore, preparing samples at a higher temperature (T = 60 °C) can significantly increase the formation rate and thickness of the PDMS coating, thereby improving the liquid repellency of the SLS. Interestingly, all SLS grafted within 10 min to 720 min exhibited ultra-low CAH (Δθ < 1.8°), and the thickness of the PDMS coating only slightly increased from 28.8 nm to 33.3 nm at 60 °C ( Figure 4E , 4F ). This indicates that the growth of PDMS polymer in this work can quickly establish equilibrium within 10 minutes at 60 °C. Subsequently, the adsorbed water produced by the reaction aggregated and significantly inhibited the condensation rate of PDMS on the surface despite the application of reduced pressure. It was observed that the SA on SLS increased slightly from 4° to 6.5°, and the duration increased from 180 minutes to 720 minutes, proving that the longer the coating time, the lower the homogeneity of the PDMS coating ( Figure 4F and Fig. 10B ).
[31] In general, the ultra-low CAH (Δθ = 1.0°) of a water drop on SLS at 60°C during 60 min indicates that the grafted PDMS polymer with a thickness of 30 nm is highly mobile and free of kinks.
[0132] Defect-free and homogeneous polymer coatings are considered important to minimize CAH. [33,37] Specifically, our method was able to form a 28.8 nm PDMS coating with chlorine-terminated PDMS (Cl-PDMS-Cl) oligomers as reactive segments within 10 min, while previous works used small molecular weight chlorosilanes for surface modification (e.g., (Me3SiO)3SiCH2CH2Si(Me)2Cl, Cl(Me2SiO) n SiMe2Cl, where n = 1-3) can only be obtained in a few nanometers (less than 5nm). [27,35,46] Thus, our vapor-phase grafting method enables much higher coverage of PDMS polymer on SLS. We demonstrate that all PDMS-grafted semi-liquid surfaces exhibit water CAs of approximately 105° with negligible deviations from five independent measurements at different locations, indicating that these SLS are chemically homogeneous ( Figure 5A and Figures 12A to 12G ). In addition, the SLS pairs made on different substrates have a 28.4 mN m -1 The low surface tension of toluene shows a small CAH ( Figure 5BThe excellent amphiphobicity of SLS with ultra-low CAH and SA is suitable for surface tensions ranging from 72.8 to 10 mN m -1 A wide range of polar or non-polar liquids ( Figure 5C Specifically, most organic liquids (e.g., toluene, hexadecane, acetone, Krytox 101, and FC72) began to slide on the SLS at a tilt angle of less than 0.6° (Table S4). At a tilt angle of 10°, acetone reached 19.9 mm s -1 High sliding speed (about 5 μL) ( FIG. 13A to FIG. 13B ). SLS on metal substrates can also repel organic liquids and water ( Figure 5B and Fig.14 ). At elevated temperatures, the viscosity of the grafted PDMS polymer on the semi-liquid surface can be significantly reduced. Therefore, heating the substrate significantly enhances the sliding behavior of the droplet. When the temperature is increased from 20°C to 80°C, the droplet sliding speed increases from 0.24 to 1.68 mm s -1 , where a 5 μL hexadecane droplet was applied at a 3° tilt angle ( Figure 5D and Figures 15A to 15B ). Increased sliding speed was also observed on SLIPS (anodized aluminum oxide (AAO) substrate impregnated with Krytox101) at elevated temperatures. Here, hexadecane was used for demonstration due to its high boiling temperature (287°C). This suggests that reducing the viscosity of the grafted semi-liquid polymer can significantly enhance molecular mobility and reduce the relaxation time of the tethered PDMS molecular chains, thereby improving liquid repellency. [30,47] Meanwhile, due to the rapid evaporation of the lubricant of Krytox 101, the droplets were fixed on SLIPS after being heated to 110 °C. Figure 5E Display with 10mN m -1 In addition, the repellency of complex fluids is studied to show the broad impact of the newly developed surface. SLS on silicon and aluminum can easily repel crude oil, mineral oil and urine ( Figures 5E to 5G ). In contrast, all of these liquids spread on the bare substrate, leaving a large wet footprint. The repellency of crude oil achieved by SLS on metals is important for petroleum applications, while the non-stick surface for mineral oils is important for kitchens. Rapid urine removal is highly desirable for saving water in toilets and for potential biomedical applications.
[0133] SLS has the potential to solve the long-standing problem of the durability of liquid-repellent surfaces. Superamphiphobic surfaces or liquid-infused surfaces rely on topographic textures to lock in air or liquid lubricants for repelling water and oil. However, high temperatures, abrasion, and scratching can cause lubricant loss or structural damage. In this paper, to demonstrate the durable liquid repellency of SLS to water and oil, comprehensive durability tests ( Figures 6A to 6G ,as well as Figures 16A to 16C and Figures 17A to 17B ). As a comparison, SLIPS made of Krytox101-infused black silicon were tested. First, heating generally causes liquid repellency failure due to lubricant loss. After continuous heating at 105°C on a hot plate for more than 3 months, SLS showed no change in liquid repellency to water and hexadecane ( Figures 16A to 16C ), while SLIPS lost liquid repellency after 3 minutes due to partial evaporation of the lubricant. Secondly, abrasion can often easily damage the surface nanotexture. After adding a 200g load in the abrasion test, SLIPS lost liquid repellency after 10 cycles, while SLS was still able to repel water and hexadecane after 1000 cycles ( Fig. 6A , 6C 、6E、 Figures 17A to 17B ). Third, for liquids and solids on the surface, reducing adhesion is believed to be important. Liquid-infused surfaces can also reduce adhesion, but they lose liquid repellency after about 200 cycles due to surface texture damage and loss of lubricant ( Figures 17A to 17B ). SLS can reduce adhesion and maintain liquid repellency after 1000 cycles ( Figure 6B , 6D , 6F). Fourth, scratching can also cause liquid repellent surface failure. Physical scratching can increase the contact line fixed on the surface, thereby causing large CAH.
[33] However, both water and oil droplets can slide off the scratched SLS, which is obtained from the dense semi-liquid polymer layer ( Figure 6G Compared to existing liquid-repellent surfaces, the unprecedented durability of SLS will undoubtedly increase the possibility of broadening engineering applications.
[0134] Such durable SLSs that exhibit non-sticky properties to different liquids are valuable for engineering applications. Here, we show two application examples of long-term fog capture and self-cleaning. Since hydrophobic surfaces (HPS) and liquid-infused surfaces have been extensively studied in fog capture, we compare SLS (made on silicon) with SLIPS (mineral oil-infused black silicon) and HPS (PTFE-coated silicon) in fog capture ( Fig. 7A). Mineral oil is used instead of Krytox 101 as a lubricant to make SLIPS because it has better water-capturing properties.
[48] The contact angles of water droplets on HPS, SLS, and SLIPS are 108.8°, 106.0°, and 103.6°, respectively. This indicates that their static wetting behaviors are close to each other. However, the CAH of water on those surfaces are 18.6°, 1.0°, and 1.1°, respectively ( Fig.18 ). We first tested the continuous fog capture at the 4th hour. The performance of SLS was comparable to that of SLIPS, while HPS failed to capture water efficiently due to its large CAH ( Figure 7C More importantly, after 4 hours, the fog-catching performance of SLS was still as good as at the beginning, but most of the water droplets captured on SLIPS were pinned on the surface due to the depletion of the liquid lubricant ( Figure 7C ). This clearly shows that our SLS is durable in long-term fog capture applications. To quantify the fog capture rates of the three surfaces, we compared the fog capture rates from 0 to 20 minutes and the fog capture rates from 240 to 260 minutes ( Fig.7D ). SLS still showed 11.07 kg h after 4 hours. -1 m -2 This is in contrast to the high efficiency of fog capture rate of 11.22 kg h in the first 20 minutes. -1 m -2 The fog capture rate is close to ( Fig.7D The changes in water CA (from 106.0° to 105.9°) and CAH (from 1.0° to 1.2°) on SLS were negligible, indicating high long-term water capture stability ( Fig.7D and Fig.18 However, the fog capture rate of SLIPS dropped from 10.61 to 2.05 kg h -1 m -2 , reduced by 81% ( Fig.7D The increase in water CA from 103.6° to 149.7° indicates that the capacity of SLIPS is reduced due to the expulsion of lubricant and the movement of droplets ( Fig.7D Meanwhile, after long-term fogging, the water CAH on SLIPS increases significantly from 1.1° to 38.6°, indicating that the lateral adhesion of the droplet to the surface (F LA ) is very big( Fig.18 The reason is that CAH reflects the F of the droplet on the surface. LA The main criterion is as follows, as described in equation (1) according to Furmidge's relation:
[49]
[0135] F LA =2aγ(cosθrec -cosθ adv ) (1)
[0136] where a is the basic contact radius of the droplet with the surface and γ is the surface tension of the liquid. As shown, the lower the CAH, the easier it is to remove the droplet from the surface (smaller F LA ), the better the slip for liquid repellency. In comparison, the fogging rate of HPS in the first 20 minutes (PTFE-coated surface, 5.4 kg h -1 m -2 ) is about 53% lower than the fog capture rate of SLS, indicating that the water absorption rate is relatively slow ( Fig.7D ). In addition, we study the dynamics of droplets on those three surfaces ( Fig. 7E ). Quantify the gravity-driven shedding characteristics of different surfaces based on the average shedding radius / frequency
[50] (Statistics are obtained from the first 20 minutes before SLIPS shows significant lubricant loss during fog capture, Fig. 7E In the first 20 minutes, both SLS and SLIPS showed low fixation on water droplets, showing small shedding radii of 0.61 mm and 0.52 mm, respectively, due to the low CAH of water ( Figure 7B , Fig.18 ). At the same time, the shedding frequency displayed by SLS is 0.42s -1 Higher than SLIPS’s 0.24s -1 , indicating that the water absorption efficiency is much higher ( Fig. 7E As a comparative HPS, the PTFE coated surface with a water CA of 108.8° and a CAH of 18.6° showed a large shedding radius of 1.82 mm and a shedding radius of 0.007 s. -1 The minimal shedding frequency is due to the large lateral adhesion on the surface (i.e., large CAH, Fig. 7E and Fig.18 )cause.
[0137] Self-cleaning, transparent, and liquid-repelling surfaces are highly desirable for solar panels, buildings, and cars. Therefore, we compared the self-cleaning properties of SLS, SHS, SLIPS, and bare glass. The four surfaces showed water contact angles of 104.9°, 152.3°, 108.5°, and 33.0°, respectively. Figure 7F , 7G and Figures 19A to 19G ). In this paper, iron oxide powder containing nano-sized particles with a particle size of less than 5 μm is used as the "contaminant". There is no physical structure on the SLS and the surface is tethered to the liquid-like flexible PDMS polymer. Particles can hardly enter the dense polymer layer on the SLS, so water droplets can slide off and thoroughly clean the surface by carrying away the particulate contaminants without leaving any dust ( Figure 7FHowever, contamination occurred on SHS, SLIPS, and bare glass ( Figure 7G and Figures 19A to 19G When the contaminant size is smaller than the gaps between the micro / nano structures on the SHS, small contaminant particles can enter the structure. The deposited contaminants change the surface chemistry, leading to air lubricant expulsion and self-cleaning failure ( Figures 19A to 19G ). At the same time, the loss of air lubricant will eventually induce the wettability on SHS to change from the Cassie-Baxter state to the Wenzel state. On SLIPS, a viscous liquid lubricant is used to physically impregnate the surface structure so that small contaminant particles are wrapped by the liquid lubricant. This makes the surface difficult to clean ( Figures 19A to 19G ). In addition, the contaminant coating will accelerate the loss of lubricant on SLIPS and induce self-cleaning failure. Water wets bare glass due to its hydrophilicity and cannot make the surface self-cleaning. Therefore, we demonstrate that SLS outperforms the current state-of-the-art technology in fog capture and self-cleaning applications.
[0138] In conclusion, we have successfully developed a robust strategy for one-step fabrication of transparent SLS to achieve durable liquid repellency. The tethered flexible PDMS polymer with a thickness of 30 nm exhibits excellent liquid-like lubricity at the liquid-solid interface. The newly developed SLS is able to repel liquids with unprecedented strengths ranging from 72.8 to 10 mN m -1 Liquids with a wide range of surface tensions, such as water, ultra-low surface tension liquids (such as FC72 and Krytox101), and complex fluids (such as crude oil and urine). More importantly, SLS exhibits impressive persistence in liquid repellency compared to state-of-the-art liquid repellent surfaces (such as liquid-injected surfaces and superhydrophobic surfaces) based on long-term fogging, self-cleaning, heating, abrasion, and adhesion tests. We have also demonstrated that SLS can be made on different substrates with optical transparency (such as silicon, glass, and metal). Although our work uses grafted PDMS as an example, in principle, any liquid-like amorphous polymer with high mobile chains can form such SLS. The repellency of SLS to crude oil can reduce drag in oil transportation, the non-sticky properties for mineral oil can alleviate contamination in the kitchen, and rapid urine removal is highly required for flush toilets to save clean water. In addition to the demonstration in this work, we envision that SLS can pave the way for potential applications such as drag reduction, anti-fouling, anti-icing, droplet condensation, and water capture.
[0139] Figures 3A-3G .Multifunctional semi-liquid surface (SLS) with durable liquid repellency. Figure 3A : Single-step autocatalytic grafting of chlorine-terminated PDMS polymers (20-50 cSt, molecular weight 2000-4000) onto hydroxylated substrates. Figure 3B : Schematic diagram of droplet sliding on the tilted SLS. Figure 3C and 3D :3D AFM image of glass surface coated with small molecule chlorosilane ( Figure 3C ) and SLS on glass grafted with flexible PDMS polymer ( Figure 3D ). Figure 3E : SLS with glass substrate at a tilt angle of 10° and 2 μL Krytox101 (γ = 17 mN m -1 ) and 20 μL water (γ=72.8 mN m -1 )’s time-series images of liquid repellency. Figure 3F : Comparison of water CAH on SLS with silicon substrate and SLIPS fabricated by infusion of Krytox 101 as a function of heating time at 105 °C. The inset shows that a 5 μL water droplet is fixed on SLIPS after 3 minutes due to lubricant evaporation, but remains movable on SLS after more than 3 months. Figure 3G : UV / Vis spectra of SLS on glass and bare glass, showing the optical transparency of SLS.
[0140] Figures 4A-4F .Chemical composition and synthesis optimization of grafted PDMS polymers for fabricating SLS. Figure 4A : ATR-FTIR spectroscopy, and Figure 4B : SEM image of the cross-sectional view of SLS on silicon (grafting time: 60 min, and grafting temperature: 60°C). Figure 4C : θ of the water drop on SLS adv ,θ rec and CAH, and ( Figure 4D ) The corresponding PDMS thickness measured by ellipsometry. The grafting time was 60 minutes. ( Figure 4E )θ of a water droplet on SLS adv ,θ rec and CAH, and ( Figure 4F ) The corresponding PDMS thickness measured by ellipsometry. The grafting temperature is 60°C. Figure 4C )and( Figure 4E ) The dotted line marked inside represents the 5° water CAH, which indicates that if the CAH is less than 5°, the surface liquid repellency is good. ( Figure 4D )and( Figure 4F ) shows the contact angle of a water droplet on SLS. All samples were fabricated using the gas phase in a vacuum oven.
[0141] Figure 5A-5G .Super liquid repellency of SLS on various substrates. Figure 5A : CA of water on different substrates before and after SLS coating. Figure 5B : CAH of toluene on SLS of different substrates. Figure 5C : CAH and CA of various liquids on SLS with silicon. Figure 5D : Temperature-dependent sliding velocity of 5 μL hexadecane on SLS and SLIPS (AAO infused with Krytox101) with silicon substrate at a tilt angle of 3°. Figure 5E : A ~1 μL FC72 fluorocarbon liquid droplet (γ = 10 mN m) slides down a SLS with a tilt angle of 10° -1 ) and 5 μL crude oil and mineral oil droplets, scale bar is 1 mm. Due to the rapid evaporation of the droplets, the volume of FC72 may not be accurately controlled. ( Fig. 5F )SLS silicon compared to bare silicon and ( Figure 5G ) Liquid repellency of SLS aluminum foil relative to crude oil, mineral oil, and urine on bare aluminum foil. These three liquids can slide easily on SLS but wet on the bare surface.
[0142] Figures 6A-6G .Permanent liquid repellency of water and organic liquids under harsh conditions. Fig. 6A ) Continuous abrasion test using cotton paper and Figure 6B Comparison of water CAH on SLS (fabricated on silicon) and SLIPS (black silicon infused with Krytox 101) after adhesion testing using tape. A 200 g test weight was applied to the abrasion test (schematic inset in a) and the adhesion test ( Figure 6B Schematic illustration in ). Fig. 6A )and( Figure 6B The inset image in ) shows that the water droplet is fixed on SLIPS after the abrasion test and the adhesion test. However, it remains slidable on SLS. ( Figure 6C ) abrasion test and ( Fig.6D ) Photographs of bonding tests. Fig. 6E ) abrasion test and ( Fig. 6F ) Repellency of water (dyed purple) and hexadecane (dyed orange) on SLS after adhesion testing. Figure 6G : Liquid repellency of water and mineral oil on SLS after scratch damage.
[0143] Figures 7A-7G Two application examples of SLS: fog harvesting and self-cleaning. Fig. 7A : Schematic illustration of PTFE-coated hydrophobic surface (HPS), SLS, and SLIPS. Figure 7B : Comparison of fog capture on three surfaces from 0-20 minutes. Figure 7C : Long-lasting fog capture on SLS for 253 minutes without loss of surface lubrication. Fig.7D : Fog capture rates on HPS, SLS, and SLIPS. The insets present the water CA on different surfaces before and after the fog capture test. During the fog capture test, which was performed by collecting water during the fog capture period 0-20 minutes and 240-260 minutes, the surfaces were placed vertically. Fig. 7E : Changes in average droplet shedding radius and shedding frequency on HPS, SLS, and SLIPS during fog capture from 0 to 20 minutes. The inset shows images of shedding water droplets on the three surfaces for size comparison. Scale bar: 2 mm. Figure 7F Self-cleaning of iron oxide particles on: SLS with water CA of 104.9° (made on glass), and Figure 7G Self-cleaning of iron oxide particles on a superhydrophobic surface (SHS) with a water CA of 152.3° (using commercial Coating manufacturing). Iron oxide powder with a particle size < 5 μm was used as "contaminant". The substrate was tilted at 30°.
[0144] References
[0145] [1] T.-S. Huang, SH Kang, SK Tang, EJ Smythe, BD Hatton, A. Greenthal, J. Aizenberg, Nature, 2011, 477, 443.
[0146] [2] X. Deng, L. Mammen, H.-J. Barth, D. Vollmer, Science, 2012, 335, 67.
[0147] [3] A. Tutja, W. Cui, M. Ma, JM Mabry, SA Mazzella, GC Rutledge, GH McKinley, RE Cohen, Science, 2007, 318, 1618.
[0148] [4] T. Liu, C.-J. Kim, Science, 2014, 346, 1096.
[0149] [5] X. Dai, N. Sun, S. O. Nelson, B. B. Stocking, J. Wang, S. Yang, T.-S. Huang, Science Advances (Sci. Adv). 2018, 4, eaaq0919.
[0150] [6] Y. Lu, S. Shatasivan, J. Song, CR Crick, CJ Kamard, IP Parkin, Science, 2015, 347, 1132.
[0151] [7] H. J. Zhao, D. J. Preston, Y. Zhu, E. N. Wang, Nature Reviews: Materials (Nat. Rev. Mater). 2016, 2, 16092.
[0152] [8] A. K. Epstein, T.-S. Huang, R. A. Bellisl, E. M. Boggs, J. Aizenberg, Proceedings of the National Academy of Sciences of the United States of America (Proc. Natl. Acad. Sci), 2012, 109, 13182.
[0153] [9] S. Amini, S. Kohler, L. Petrone, O. Ahanotou, S. Sanni, C. N. Sutanto, S. Huon, L. Cohen, J. C. Weaver, J. Eizenberg, Science, 2017, 357, 668.
[0154]
[10] M. J. Kreider, J. Alvarenga, P. King, J. Eizenberg, Nature Reviews Materials (Nat. Rev. Mater), 2016, 1, 15003.
[0155]
[11] S. Pan, A. K. Kota, J. M. Mabry, A. Tuthha, Journal of the American Chemical Society (J. Am. Chem. Soc). 2012, 135, 578.
[0156]
[12] D. Bonn, J. Eggers, J. Andek, J. Mounier, E. Rowley, Reviews of Modern Physics (Rev. Mod. Phys), 2009, 81, 739.
[0157]
[13] JF Oliver, C. Huha, SG Mason, Journal of Colloid and Interface Science, 1977, 59, 568.
[0158]
[14] A. Giacomello, L. Schimmel, S. Dietrich, Proceedings of the National Academy of Sciences of the United States of America (Proc. Natl. Acad. Sci. USA), 2016, 113, E262.
[0159]
[15] Dt McNajer, S. Ghosh, R. Laglau, S. Otten, A. Pitt, C. Berenson, J. Ziegers, D. van den Ende, F. Mugler, Nature Communications, 2014, 5, 3559.
[0160]
[16] ABD Cassi, S. Baxter, Journal of the Chemical Society, Faraday Transactions (Trans. Faraday Soc). 1944, 40, 0546.
[0161]
[17] RN Wenzel, Industrial and Engineering Chemistry (Ind. Eng. Chem). 1936, 28, 988.
[0162]
[18] A. Lafuma, D. Cray, Europhys. Lett., 2011, 96, 56001.
[0163]
[19] A. K. Epstein, T.-S. Huang, R. A. Bellisl, E. M. Boggs, J. Aizenberg, Proc. Natl. Acad. Sci. USA, 2012, 109, 13182.
[0164]
[20] M. Nosonovsky, V. Hegaz, ACS Nano, 2012, 6, 8488.
[0165]
[21] N. Milikovich, R. Enright, Y. Nan, K. Lopez, N. Dou, J. Sack, E. N. Wang, Nano Lett. 2013, 13, 179.
[0166]
[22] BJ Rosenberg, TV Brun, MK Fu, AJ Schmitz, Phys. Fluids, 2016, 28, 015103.
[0167]
[23] GB Huang, K. Page, A. Patil, SP Nair, E. Allen, IP Parkin, ACS Nano, 2018, 12, 6050.
[0168]
[24] X. Dai, B. B. Stocking, S. Yang, T.-S. Huang, ACS Nano, 2015, 9, 9260.
[0169]
[25] DJ Preston, Y. Song, Z. Lu, DS Anto, EN Wang, ACS Appl. Mater. Interfaces. 2017.
[0170]
[26] F. Shellenberger, J. Xie, N. Encinas, A. Hardy, M. Carappa, P. Papadopoulos, H.-J. Bart, D. Vollmer, Soft Matter, 2015, 11, 7617.
[0171]
[27] W. Chen, AY Fadeev, MC Xie, D. Honner, J. Youngblood, TJ McCarthy, Langmuir, 1999, 15, 3395.
[0172]
[28] JW Krupfer, TJ McCarthy, Langmuir. 2011, 27, 11514.
[0173]
[29] D. F. Cheng, C. Urata, B. Mashid, A. Hozumi, Journal of the American Chemical Society (J. Am. Chem. Soc). 2012, 134, 10191.
[0174]
[30] D. F. Cheng, C. Urata, M. Yagibashi, A. Hozumi, Angew. Chem. Int. Ed. 2012, 51, 2956; Angew. Chem. 2012, 124, 3010.
[0175]
[31] L. Wang, T. J. McCarthy, Angew. Chem., Int. Ed., 2016, 55, 244; Angew. Chem., 2016, 128, 252.
[0176]
[32] H. Hu, G. Liu, J. Wang, Adv. Mater. Interfaces, 2016, 3, 1600001.
[0177]
[33] S. Wu, D. Vollmer, Angew. Chem., Int. Ed., 2016, 55, 6822; Angew. Chem., 2016, 128, 6934.
[0178]
[34] L. Yu, G.Y. Chen, H. Xu, X. Liu, ACS Nano. 2016, 10, 1076.
[0179]
[35] DH Flagg, TJ McCarthy, Langmuir. 2017, 33, 8129.
[0180]
[36] P. Liu, H. Zhang, W. He, H. Li, J. Jiang, M. Liu, H. Sun, M. He, J. Cui, L. Jiang, X. Yao, ACS Nano, 2017, 11, 2248.
[0181]
[37] M. Boban, K. Golovin, B. Tobelman, O. Gupte, J. M. Mabry, A. Tuthha, ACS Appl. Mater. Interfaces, 2018, 10, 11406.
[0182]
[38] N. Singh, H. Uchida, T. Sato, R. Hernes, M. Yagibashi, C. Urata, A. Hozumi, Langmuir, 2018, 34, 11405.
[0183]
[39] G. Zhang, B. Liang, Z. Zhong, Y. Huang, Z. Su, Adv. Mater. Interfaces, 2018, 5, 1800646.
[0184]
[40] X. Zhong, H. Hu, L. Yang, J. Sheng, H. Fu, ACS Appl. Mater. Interfaces, 2019.
[0185]
[41] S. Wu, H. J. Barth, Angew. Chem., Int. Ed., 2017, 56, 4965; Angew. Chem., 2017, 129, 5047.
[0186]
[42] RAL Jones, Nature Materials, 2003, 2, 645.
[0187]
[43] M. Kuniyoshi, M. Takahashi, Y. Tokuda, T. Yoko, Journal of Sol-Gel Sci. Technol., 2006, 39, 175.
[0188]
[44] D. Bodas, C. Khanmelek, Microelectron. Eng., 2006, 83, 1277.
[0189]
[45] M. Mahmudi, H. Javaherianagash, Journal of Adhesion Science and Technology (J. Adhes. Sci. Technol), 2015, 29, 1341.
[0190]
[46] AY Fadeev, TJ McCarthy, Langmuir. 2000, 16, 7268.
[0191]
[47] C. Luap, W. A. Gödel, Macromolecules. 2001, 34, 1343.
[0192]
[48] K.-C. Parker, P. Kim, A. Greenthal, N. Ho, D. Fox, J. C. Weaver, and J. Aizenberg, Nature, 2016, 531, 78.
[0193]
[49] C. Fomich, Journal of Colloid Sci. 1962, 17, 309.
[0194]
[50] D. Ballantien, R. Dey, H. Houck, D. van den Ende, and F. Mugler, Phys. Rev. Lett., 2018, 120, 214502.
[0195] Supplementary experimental results
[0196] Various movies are collected to show different aspects of the disclosure.
[0197] Movie S1 shows the effect of a semi-liquid surface and bare glass on the low surface tension liquid Krytox101 oil (γ = 17.0 mN m -1 ) and water (γ=72.8mN m -1 ) liquid repellency. The semi-liquid surface modified glass maintains optical transparency and liquids may slide off easily. However, liquids leave a wet footprint on the bare glass surface. AFM images show the ultra-smooth surface of SLS compared to bare glass.
[0198] Movie S2 shows the FC72 (γ = 10 mN m) on a semi-liquid surface. -1 )、Krytox101(γ=17mN m -1 ), acetone (γ=25.2mN m -1 ) and water (γ=72.8mN m -1 ) for various liquid sliding speeds. In order to make the entire FC72 and Krytox101 droplets visible in the screen, ~1 μL FC72 and 2 μL Krytox101 were used instead of 5 μL drops. Due to the rapid evaporation of the droplets, the FC72 volume may not be accurately controlled.
[0199] Movie S3 shows that the sliding velocity of hexadecane on the semi-liquid surface and the liquid-injected surface increases with increasing temperature. This indicates that the grafted semi-liquid polymer can significantly enhance the molecular mobility of the tethered PDMS molecular chains at high temperatures, leading to improved liquid repellency. However, the liquid-injected surface cannot withstand high temperatures due to the loss of lubricant.
[0200] Movie S4 shows that semi-liquid surfaces fabricated on silicon or aluminum can easily repel different liquids, even for a composite fluid of crude oil and urine. In contrast, all of these liquids spread on the bare substrate, leaving a larger wet footprint. Here, water shows a faster sliding speed because: (i) the viscosity of water is low, and (ii) the contact area of the water droplet is smaller due to the larger contact angle of the water droplet compared to the other liquids.
[0201] Movie S5 shows the durable liquid repellency of the semi-liquid surface to water and oil even after a heating test lasting more than 3 months at 105° C. This indicates that the thermal stability of the grafted semi-liquid PDMS polymer is high due to the strong bond dissociation energy of Si—O between the PDMS molecules and the substrate.
[0202] Film S6 shows the durable liquid repellency of the semi-liquid surface to water and hexadecane even after 1000 cycles of an abrasion test in which tissue paper was stuck to the bottom of a 200 g load. The semi-liquid surface showed low friction during the entire test.
[0203] Film S7 shows the durable liquid repellency of the semi-liquid surface to water and hexadecane even after 1000 cycles of the bonding test, in which the strong tape bonded to the bottom of a 200 g load. The semi-liquid surface showed low adhesion throughout the test.
[0204] Movie S8 shows the durable liquid repellency of the semi-liquid surface to water and mineral oil even after a scratch test, where a sharp scraper is used to scratch the surface. Both water droplets and oil droplets can slide off the scratched semi-liquid surface, benefiting from the densely coated semi-liquid PDMS polymer layer on the surface. Here, we use mineral oil to show that SLS can repel various hydrocarbon liquids.
[0205] Movie S9 shows a comparison of the fog capturing performance of a semi-liquid surface, a PTFE-coated hydrophobic surface, and a liquid-infused surface (SLIPS), where the semi-liquid surface shows persistent and effective fog capturing properties even after more than 4 hours. However, SLIPS exhibits lubricant loss on the surface after 4 hours. Also, the hydrophobic surface shows a low water capture rate during the entire process.
[0206] Movie S10 shows a comparison of the self-cleaning properties of a semi-liquid surface, a superhydrophobic surface (SHS), a liquid-injected surface (SLIPS), and a bare surface. At the beginning, it appears that SLS, SLIPS, and SHS can repel water extremely well, indicating that all of these surfaces are in good conditions before the self-cleaning experiment, while only SLS can repel acetone liquid with low surface tension. Then, iron oxide powder (particle size <5 μm) is used as a "pollutant". This shows that particles on the semi-liquid surface can be completely carried away by water droplets without leaving any dust, however, the other three surfaces cannot self-clean.
[0207] Fabrication of semi-liquid surfaces on various substrates: Semi-liquid surfaces were fabricated by tethering flexible polymer molecules to solid substrates using a single-step autocatalytic grafting method. Specifically, the oxygen plasma treated substrate was placed face down on the lid of a petri dish. Then, a petri dish (size: 150 mm diameter, 15 mm height) containing 800 μL of liquid Cl-PDMS-Cl was placed in a vacuum oven (0.15 Torr) at 60°C for 60 minutes. The liquid was evenly dispersed on the surface of the petri dish by gently shaking it before placing it in the vacuum oven. This single-step gas phase method (i.e., no direct contact between the substrate and the liquid reagent) can graft PDMS molecules on a solid substrate. The substrate was rinsed sequentially with sufficient isopropyl alcohol (IPA), acetone, and water. It should be noted that liquid phase reactions (i.e., contacting the substrate with the liquid reagent) can also be applied to make the grafting successful. Unless otherwise specified, all SLS samples were prepared in the gas phase at 60°C for 60 minutes ( Figure 8 ).
[0208] Fabrication of control surfaces: Control studies were performed using hydrophobic, superhydrophobic, and liquid-infused surfaces. Trimethylchlorosilane-coated hydrophobic glass slides were prepared using the vapor phase in a vacuum oven at 60°C for 12 hours. This surface was used for morphological comparison with SLS on glass ( Figures 3A-3G ). Polytetrafluoroethylene (PTFE)-coated silicon was fabricated by sputtering with a treatment time of 20 minutes and a power of 100 W. This surface was used as a hydrophobic surface for comparison with SLS and SLIPS for fog capture ( Figures 7A-7G ). The black silicon substrate was prepared according to the method reported in our previous work. [S1] And then, trimethylchlorosilane was used to salt the sample. This surface was used to make SLIPS. Then, a lubricant such as Krytox 101 or mineral oil was injected into the salted black silicon, and a spin coater (WS-650-23NPP, Laurell) was used to remove the redundant lubricant for the liquid-injected surface (i.e., SLIPS). This surface was used to contact the surface for heating, abrasion, and bonding ( Figures 3A-3G and 6A-6G) and fog capture ( Figures 7A-7G ) was compared with SLS in a harsh durability test. Figures 19A-19G ), a thin layer of PDMS prepolymer mixed with a curing agent (10:1 ratio of base to curing agent) was spin coated on a glass slide (2000 rpm, 30 seconds), and then cured at 80° C. for 4 hours. Thereafter, the PDMS organogel-coated glass slide was immersed in 10 cSt silicone oil for 48 hours to fully expand the PDMS network to infuse the lubricant. [S2]Finally, excess silicone oil on the surface was removed by spin coater (2000 rpm, 30 seconds) or by compressed air. This surface was used for comparison with SLS for self-cleaning tests ( Figures 7A-7G ). By two-step spraying from commercial The super-hydrophobic glass slides were made from the solution and also used to compare with SLS for self-cleaning test ( Figures 7A-7G ).
[0209] Surface characterization: All substrates were treated with 200 mTorr O2 gas at 200 W for 20 minutes in an oxygen plasma cleaner (PX-250, March Asher) before PDMS grafting. The optical transparency of these surfaces was studied at a resolution of 1 nm using a PerkinElmer Lambda 900 UV-Vis / NIR spectrophotometer with a wavelength range of 200 nm to 900 nm. The chemical composition of the surface before and after grafting with PDMS polymer was studied using an FT-IR / ATR spectrometer (Nexus 4700, Nicolet). Atomic force microscopy (AFM) measurements were performed in tapping mode using a Nanoscope V controller on a multimode microscope (Multimode IV, Bruker). The thickness of the SLS on silicon was characterized by scanning electron microscopy (SEM, Supra-40, Zeiss) and Sentech 800 ellipsometer at 70° incident angle and with He-Ne laser (λ=632.8 nm) as light source. The thickness was calculated using the Cauchy model, using a SiO2 layer of the stated thickness on oxygen plasma treated silicon as a baseline layer. The average thickness was obtained by taking 5 independent measurements at different locations on the SLS. High temperature durability tests at 105°C were performed using a hot plate (PC-400D, Corning).
[0210] Contact angle measurements: Contact angle measurements were performed at room temperature under ambient conditions (20-22°C, ~40% relative humidity) using a contact angle measurement system (Model 290, Rame-hart). All contact angle values were derived from an average of at least 5 independent measurements by applying a ~5 μL droplet on the test platform. For contact angle hysteresis measurements, the surface was tilted relative to the horizontal until the droplet began to slide along the surface. Then, the advancing, receding and sliding angles of the droplet were calculated by a computer program, where the droplet was contained in a spherical cap.
[0211] Fog capture and self-cleaning experiments: In order to conduct a better comparative study of fog capture, hydrophobic surfaces (HPS, PTFE-coated silicon), SLIPS (black silicon infused with mineral oil) and SLS (PDMS-grafted silicon) with the same size of 1.4×3.3 mm were vertically fixed at the same height. A commercial ultrasonic humidifier (EE-5301, Crane) was used to generate mist. The mist flow was directed to the vertically suspended surface at an angle of 45°±5°, and the distance between the mist outlet and the vertical substrate was ~20 cm. The image of the absorbed water droplets can be obtained from a snapshot of a video recorded using a digital SLR camera (D5600, Nikon) equipped with a zoom lens (AF zoom-NIKKOR 24-85mm f / 2.8-4D IF lens, Nikon). We can get the projection of the droplet from the recorded image, that is, the width (W) of the droplet. We assume that the absorbed water droplet can be roughly contained in the spherical cap, so the shedding radius (R) of the water droplet, that is, the base contact radius of the droplet with the surface can be calculated as R = W / 2. [S3] By measuring the surface area of 7.5cm in a period of time (t), 2 The number of droplets (N) sliding on the surface of (3cm×2.5cm) is counted to obtain the droplet shedding frequency (f), which can be described as f=N / t. A clean beaker is placed under the drainage outlet of the substrate to collect the dripping water. Water collection begins after the first droplet slides off the surface. Then, the weight of the beaker before (m0) and after (m1) the water collection time (t) is measured by an analytical balance. The average fog capture rate can be calculated as (m1-m0) / (t·A), [S1] Where A is the surface area of the substrate and t is 5 minutes. All fog capture data mentioned above are averaged from at least 5 independent measurements. In order to achieve better visibility in the self-cleaning test, a transparent glass substrate was used, in which super hydrophobic glass ( Coating), SLIPS (organogel infused with silicone oil) and clean glass slides as comparison substrates for SLS (PDMS grafted glass). A similar amount of iron powder was sprinkled on the substrate, and then slightly pressed to simulate stubborn contaminant dust, and then the substrate was washed with continuous water droplets (tilt angle of 30°). A digital camera was used to record the entire self-cleaning process.
[0212] Material supply: Chlorine-terminated polydimethylsiloxane (Cl-PDMS-Cl, viscosity: 20-50 cSt at 25°C, M w: 2000-4000), trimethylchlorosilane (Me3SiCl), silicone oil (viscosity: 10 cSt at 25°C), PDMS silicone elastomer with independent hydrogen silane curing agent were all purchased from Galester Co., Ltd. Krytox GPL 101 (Krytox101) and FC72 fluorocarbon fluids were obtained from Dupont Inc and Synquest Laboratories, respectively. Other liquids including ethanol (>99.0%), isopropyl alcohol (IPA, >99.5%), acetone (≥99.5%), tetrahydrofuran (THF, ≥99.9%), hexadecane (≥99%), toluene (≥99.5%), dimethylformamide (DMF, ≥99.8%), sulfuric acid (H2SO4, 95.9wt%), triethylamine (TEA, ≥99%), and urine were supplied by VWR. White mineral oil was purchased from Sonneborn Inc. Crude oil samples from the Denver / Julesburg Basin (USA) were provided by Brighton Colorado Weld. Iron (II, III) oxide powder (<5 μm, 95%) used as contaminant in the self-cleaning test was purchased from Sigma-Aldrich Inc. Crystal violet water-soluble dye (purple) and Sudan I oil-soluble dye (orange) were supplied by VWR. All chemicals were used as received without further purification. Cotton paper (single-ply lightweight), double-coated paper tape (401M, 3M TM ) and ordinary microscope slides (25×75 mm, 1.1 mm thickness) were purchased from VWR. Test weights (200 g) were purchased from McMaster-Carr Inc. Test grade p-type silicon wafers (100 orientation) with a diameter of 4 inches and a thickness of ~300 μm were purchased. Metal (Ti, Fe, Ni, Cr) deposited silicon wafers were made by electron gun evaporator (Temescal 1800 electron beam evaporator), where the metal layer thickness was 100 nm, where 50 nm Cr was used as an adhesion layer for Ti, Fe and Ni layers. Commercial aluminum foil purchased from VWR was used without treatment. Deionized (DI) water was prepared by using a Milli-Q water purification system (Millipore).
[0213] Table S1. Comparison of liquid repellency between the semi-liquid surface (SLS) fabricated in this work and other amphiphobic surfaces
[0214]
[0215]
[0216] [a] Surface tension at 20°C
[0217] Table S2. Surfaces prepared from chlorine-terminated PDMS polymers under different conditions and their repellency to high surface tension liquid water (72.8 mN m at 20 °C). -1 )
[0218]
[0219] Table S3. Surfaces prepared from chlorine-terminated PDMS polymers under different conditions and their repellency to low surface tension liquid toluene (28.4 mN m at 20 °C). -1 )
[0220]
[0221] Various samples prepared by different reaction systems (with or without solvent and catalyst additives) and multiple reaction conditions were studied to obtain the optimal preparation parameters for SLS. As shown in Tables S1 and S2, for different samples of Samples No. 1 to 6, the CAH of water and toluene was obtained by contact angle measurement. For Samples No. 1 and No. 2, Cl-PDMS-Cl and H2SO4 acid catalyst or TEA base catalyst were added to IPA, where the mass ratio was 10:1:89 (Cl-PDMS-Cl: (H2SO4 or TEA): IPA) to form a coating solution. For Sample No. 3, only Cl-PDMS-Cl was added to IPA, where the mass ratio was 10:90. For Sample No. 4, Cl-PDMS-Cl was directly used as a coating agent. Next, several drops of coating solutions No. 1 to No. 4 were applied to four inclined hydroxylated silicon substrates respectively using a pipette. The reactions of No. 1 to No. 4 were carried out at 20°C and dried for 60 minutes. For samples No. 5 and No. 6, the hydroxylated silicon substrate was placed in a Petri dish in contact with (No. 5) or not in contact with (No. 6) liquid Cl-PDMS-Cl, i.e., liquid phase (No. 5) or gas phase (No. 6) reaction, and then the Petri dish was covered and placed in a vacuum oven heated at 60°C for 60 minutes. After the reaction, all samples were rinsed continuously with sufficient IPA, acetone and water. Finally, contact angle measurements were performed to obtain the optimal preparation parameters. It should be noted that the liquid phase reaction (sample No. 5) or gas phase reaction (No. 6) under reduced pressure at 60°C can provide much lower CAH to water and toluene than other substances. Therefore, the liquid phase or gas phase (No. 5 or No. 6) under reduced pressure at 60°C can be used as the optimal preparation parameters for SLS.
[0222] Table S4. CA (θ) of droplets (5 μL) with different surface tensions on semi-liquid surfaces (SLS) A / θ R), CAH (Δθ) and sliding angle (SA).
[0223]
[0224]
[0225] [a] Surface tension at 20°C [mN m -1 [b] Due to rapid evaporation of the droplets, the SA value may not be achieved accurately.
[0226] Figure 8 Schematic diagram of the gas phase preparation of SLS in a vacuum oven, where the hydroxylated substrate is bonded to the inner wall of a Petri dish lid.
[0227] Fig. 9A -C. Silicon before and after PDMS grafting ( Fig. 9A ) and glass( Fig. 9B ) surface, where lower roughness can be obtained after PDMS coating. Fig. 9C : SEM images of cross-sectional views of silicon before and after PDMS grafting, where a ~30 nm PDMS polymer layer can be observed on the SLS fabricated on a silicon wafer substrate.
[0228] Fig. 10A -B. At different coating temperatures ( Fig. 10A ) with 60 minutes coating time and different coating times ( Fig. 10B ) Sliding angle (SA) of a 5 μL water droplet on SLS with silicon prepared in a vacuum oven with 60°C coating temperature.
[0229] Fig.11 . Schematic diagram showing the possible effect of temperature on the evaporation of liquid Cl-PDMS-Cl in a vacuum oven. Combined with the water CAH data, a much lower evaporation rate is presented when the temperature is less than or equal to 45°C, and a much higher evaporation rate is presented when the temperature is greater than or equal to 60°C.
[0230] Fig. 12A - G. Images of water (5 μL) contact angles on different substrates before and after PDMS coating. It should be noted that all PDMS coated surfaces of SLS present similar water CA of -105°, indicating chemical homogeneity of the PDMS coatings on these surfaces.
[0231] Fig.13A -B: Fig.13A : Time-series images of different droplets sliding down the SLS with silicon at a tilt angle of 10°. Fig. 13B: Sliding speed of different liquids (5 μL) on SLS with silicon at a tilt angle of 10°. The scale bar in (a) is 1 mm.
[0232] Fig.14 .Contact angle hysteresis (CAH) of water on SLS fabricated on metal surfaces.
[0233] Fig.15A -B: Displays SLS at different temperatures ( Fig.15A ) and SLIPS( Fig. 15B ) Time-lapse images of a hexadecane droplet sliding on a 2D image.
[0234] Fig.16A -C: Schematic diagram of high temperature aging test heated at 105°C ( Fig.16A ) and digital photos ( Fig. 16B ). Fig. 16C : Liquid repellency of SLS to water (dyed purple) and hexadecane (dyed red) after high temperature aging for more than 3 months.
[0235] Fig.17A -B: shows SLIPS before and after harsh durability tests of high temperature aging, abrasion, and adhesion for different durations ( Fig.17A Black silicon injected with Krytox101) and SLS ( Fig. 17B , images of the surface of PDMS-grafted silicon).
[0236] Fig.18 Water CAH of PTFE-coated hydrophobic surface (HPS), SLS, and SLIPS before and after 260 min fog capture test.
[0237] Fig.19A -G. Performance of SLIPS and bare glass slides for self-cleaning. Fig.19A : Schematic diagram of the structure of transparent SLIPS, which was made by spin-coating an organogel on a glass slide and then injecting silicone oil into it. Fig.19B -C:SLIPS( Fig.19B ) and bare glass ( Fig.19C ), where both SLIPS and a bare glass slide were contaminated after the experiment. Here, iron oxide powder (particle size < 5 μm) was used as the “contaminant”. Fig.19D -E: Before pollution ( Fig.19D ) and after ( Fig.19E ) Schematic diagram of a superhydrophobic surface where contaminant particles enter the microstructure on the surface, inducing air lubricant loss. Fig.19F -G: before pollution ( Fig.19F ) and after ( Figure 19G) Schematic diagram of liquid injection into a surface where a liquid coating is formed on the contaminant.
[0238] Supplementary references
[0239] [S1] X. Dai, N. Sun, S. O. Nelson, B. B. Stocking, J. Wang, S. Yang, T.-S. Huang, Science Advances (Sci. Adv). 2018, 4, eaaq0919.
[0240] [S2] C. Gao, L. Wang, Y. Lin, J. Li, Y. Liu, X. Li, S. Feng, Y. Zheng, Advanced Functional Materials, 2018, 28, 1803072.
[0241] [S3] R. Dey, J. Gilbers, D. Ballantien, H. Hoek, D. van den Ende, F. Mugler, Appl. Phys. Lett., 2018, 113, 243703.
[0242] [S4] W. Chen, AY Fadeev, MC Xie, D. Honner, J. Youngblood, TJ McCarthy, Langmuir, 1999, 15, 3395.
[0243] [S5] JW Krupfer, TJ McCarthy, Langmuir. 2011, 27, 11514.
[0244] [S6] D. F. Cheng, C. Urata, M. Yagibashi, A. Hozumi, Angew. Chem. Int. Ed. 2012, 51, 2956; Angew. Chem. 2012, 124, 3010.
[0245] [S7] L. Wang, TJ McCarthy, Angew. Chem., Int. Ed. 2016, 55, 244; Angew. Chem. 2016, 128, 252.
[0246] [S8] L. Yu, G.Y. Chen, H. Xu, X. Liu, ACS Nano. 2016, 10, 1076.
[0247] [S9] P. Liu, H. Zhang, W. He, H. Li, J. Jiang, M. Liu, H. Sun, M. He, J. Cui, L. Jiang, ACS Nano. 2017, 11, 2248.
[0248] [S10] S. Wu, N. Encinas, D. Vollmer, H. J. Barth, Advanced Materials (Adv. Mater). 2017, 29, 1604637.
[0249] [S11] G. Zhang, B. Liang, Z. Zhong, Y. Huang, Z. Su, Adv. Mater. Interfaces, 2018, 5, 1800646.
[0250] [S12] M. Boban, K. Golovin, B. Tobelman, O. Gupte, J. M. Mabry, A. Tutja, ACS Appl. Mater. Interfaces, 2018, 10, 11406.
[0251] Additional experiments were performed on SLS grafted onto exemplary glass substrate embodiments of the present disclosure formed using various PDMS oligomer molecular weights and viscosities to examine the relationship between ice adhesion strength and water CAH ( Fig. 20 ).
[0252] The PDMS oligomer molecules used to make SLS on the substrate are trimethylsiloxy-terminated PDMS oligomers ("CH3-terminated PDMS"). PDMS oligomers of the same type but each having different viscosities and molecular weights were studied. Specifically, the viscosities of the PDMS oligomers are: 20, 50, 100, 200, 500, 1000, 5000, 30000 and 100000 cSt, and the corresponding molecular weights are: 2000, 3780, 5970, 9430, 17250, 28000, 49350, 91700 and 139000 g / mol. According to step 120, the original glass slide substrate is washed with acetone and treated with oxygen plasma for 10 minutes. Subsequently, according to steps 110 and 115, the plasma-treated glass slide is immersed in CH3-terminated PDMS liquids each having the various molecular weights mentioned above for 12 hours, and the reaction is carried out at room temperature.
[0253] Thereafter, the PDMS polymer grafted glass substrate is rinsed with toluene in a shaker for another 12 hours (step 130) to wash away the ungrafted free PDMS oligomers from the substrate. As indicated by the visual appearance of the absence of any liquid on the surface, the free PDMS oligomers are substantially completely rinsed away. As disclosed elsewhere herein, in the case of step 130, if the free PDMS oligomers are not completely removed, it may be beneficial because this may beneficially generate interfacial free molecules and thereby enhance liquid or ice removal. If desired, the amount of the interfacial free molecules can be manipulated by varying the rinse time, for example, from 0 to 12 hours, thereby adjusting the relative amount of free PDMS oligomers left on the grafted substrate surface.
[0254] The substrates with the SLS formed thereon were then air dried and used for additional studies to measure the CAH of water droplets and evaluate ice removal performance. CAH values were averaged from at least 5 independent measurements by applying a ~10 μL droplet onto the test substrate. Ice adhesion strength values were averaged from at least 5 independent measurements on the test substrate.
[0255] like Fig. 20 As shown in (open symbols), SLS substrates with low contact angle hysteresis (CAH) and low sliding angle (SA) are amphiphobic. The liquid repellency properties of SLS have been confirmed for low surface tension liquids such as acetone and toluene, as well as perfluorinated liquids such as Krytox 101, FC40, HFE7100, FC72, R134a, and R410A. The CAH of water follows a trend of increasing with increasing viscosity / molecular weight of the PDMS polymer used.
[0256] like Fig. 20As depicted in (closed symbols), the ice removal performance of the SLS substrates shows a parabolic curve as a function of the viscosity / molecular weight of the PDMS oligomer used, with the lowest ice adhesion strength recorded for the sample with a molecular weight of 17,250 g / mol (500 cSt viscosity) (τ=22.6±4.8 kPa), and the CAH on the substrate with SLS formed using a PDMS oligomer of this molecular weight was also less than 4°. As depicted, for lower molecular weights (2,000 to 9,430 g / mol), the CAH was less than 4° and the ice adhesion strength remained at or below about 75 kPa. At higher molecular weights (>28,000 g / mol), the CAH began to increase, which we theorize reflects an increased degree of entanglement between the PDMS polymers tethered to the substrate and increased SLS losses, as properties believed to promote liquid repellency. However, up to a molecular weight of 91,700, the CAH remains below about 6° and the ice bonding strength remains at or below about 75 kPa, and even at a molecular weight of 139,000 g / mol, the CAH and ice bonding strength are less than those of bare glass. Based on this parameter study, a CH3-terminated PDMS oligomer with a molecular weight of 17,250 g / mol (500 cSt viscosity) appears to be good or even optimal, and this type of PDMS oligomer is selected to fabricate SLS on a substrate.
[0257] Additional experiments were conducted on SLS grafted onto an exemplary aluminum substrate embodiment to examine the relationship between water CAH, PDMS oligomer molecular weight, and viscosity ( Fig.21 ).
[0258] Aluminum foil is used as substrate. Aluminum foil pieces are cut into 3 cm × 3 cm sizes, and then immersed in a solution containing a CH3-terminated PDMS oligomer liquid for 12 hours, the viscosity of the liquid being one of 50, 100, 200, 500, 1000, 5000, 30000 and 100000 cSt, and the corresponding molecular weight is the same as the molecular weight described above. The aluminum foil is used as is without any plasma treatment (e.g., without step 120). During immersion in the PDMS oligomer liquid, the aluminum foil substrate is kept at room temperature. Thereafter, the substrate is rinsed with toluene in a shaker for another 12 hours to ensure that ungrafted free PDMS oligomers are removed (step 130). Subsequently, the aluminum foil with SLS thereon is air-dried, and is used to study liquid repellency properties.
[0259] As measured by CAH ( Fig.21 ) and low sliding angle (data not shown), the SLS prepared in this way are amphiphobic. The CAH data of water on these surfaces follow a parabolic trend, such as Fig.21As shown in . For example, the CAH value of the SLS substrate grafted with 500 cSt PDMS oligomer is 6.2°±0.5°. The results were averaged from at least 5 independent measurements by applying a ~10 μL droplet on the test substrate. Fig.21 Although water was used to confirm successful grafting of the SLS to the substrate, the liquid repellent functionality can be extended from water to organic liquids or other complex fluids, similar to what is described elsewhere in this article.
[0260] Additional experiments were performed on SLS grafted onto exemplary glass substrate embodiments of the present disclosure using semi-liquid solvent mixtures with different ratios of PDMS and inert liquid to examine ice adhesion strength ( Fig. 22 ).
[0261] Heptane was used as an inert liquid to reduce the viscosity of the CH3-terminated PDMS oligomer and reduce the cost to make it more suitable for use as a spray solvent. For initial studies, the solvent was prepared by mixing a CH3-terminated PDMS oligomer liquid with a viscosity of 500 cSt (MW = 17,250 g / mol) with n-heptane at a volume ratio of 1:10 PDMS oligomer:heptane. When compared to a semi-liquid surface (i.e., pure PDMS oligomer) made on glass with a mixture ratio of 1:0, both surfaces showed ice adhesion strengths with values comparable to Fig. 22 The values shown in are similar. These data are from a 12 hour immersion time followed by a 12 hour rinse time. The data show that a mixture of PDMS and n-heptane can produce SLS grafted on a substrate with similar ice bond strength functionality as SLS grafted on a substrate using pure PDMS. Although we used n-heptane as an exemplary inert liquid, other inert liquids may also work as discussed elsewhere herein.
[0262] In another experiment, a mixture of CH3-terminated PDMS oligomer liquid and heptane (1:10 ratio of PDMS:n-heptane) was used as a spray solution to form SLS grafted on a glass substrate that was not given plasma treatment (e.g., without step 120). A pristine glass slide without any plasma treatment was sprayed with the mixture and allowed to stand for 12 hours. The glass slide was then rinsed with toluene in a shaker for 5 minutes (step 130). The water CAH of the substrate with SLS grafted thereon was 4.1°±0.4° and the ice bonding strength was 3.96 kPa. These results indicate that a solution of PDMS and an inert liquid can be applied to a substrate surface to produce SLS on a glass substrate without plasma treatment. Without being limited by theory in the scope of the present disclosure, it is believed that aluminum and glass substrates or other substrates having an oxide layer thereon (e.g., metal oxides, silicon oxide, titanium oxide, zinc oxide, etc.) can provide natural or inherently hydroxylated surfaces having sufficient hydroxyl functional groups thereon for successful PDMS grafting, thereby greatly expanding the utility of the methods and SLS grafted article formation as disclosed herein.
[0263] Those skilled in the art to which this application relates will appreciate that other and further additions, deletions, substitutions and modifications may be made to the described embodiments.
Claims
1. A method comprising: providing a substrate having a surface, wherein the surface is hydroxylated; and The hydroxylated surface of the substrate is exposed to a PDMS oligomer having the formula: R1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-R2 in: Said R1 and R2 both include: -(CH2) m -R3, R3 is one of -Cl or -SiCl3, The m is an integer in the range of 0 to 10, The n is an integer in the range of 10 to 500, and The R3 in the PDMS oligomer undergoes hydrolysis, so that HCl automatically generated by the hydrolysis causes one terminal Si atom in the PDMS oligomer to covalently bond to the hydroxylated surface through a self-catalyzed condensation reaction to form a PDMS polymer grafted layer on the surface. 2 . The method according to claim 1 , wherein both of said R1 and R2 have the same one of said R3. The method according to claim 1 , wherein said R1 and R2 have different one of said R3 .
4. The method of claim 1, wherein providing the substrate comprises providing a substrate consisting of: silicon, glass, cross-linked PDMS organogel, Al, Ti, Fe, Ni or Cr metal, or a multilayer combination thereof.
5. The method of claim 1, wherein the exposure is for a period of time in the range of 5 to 720 minutes. The method of claim 1 , wherein the exposing occurs inside a container in which the substrate is housed.
7. The method of claim 6, wherein the container is configured to maintain the interior of the container at a temperature value in the range of 20 to 100°C.
8. The method of claim 6, further comprising the presence of acid vapor in the container.
9. The method of claim 1, wherein the exposing comprises exposing to the PDMS oligomer in a liquid phase.
10. The method of claim 9, wherein the water concentration in the liquid phase is less than 1 wt%.
11. The method of claim 1, further comprising forming the hydroxylated surface on the substrate surface comprising exposing the substrate surface to oxygen plasma treatment, corona treatment, a strong oxidizing solution, or a combination thereof.
12. The method according to claim 11, wherein: The oxygen plasma treatment includes applying a power setting in the range of 20 to 300 W, an O2 pressure in the range of 50 to 300 mTorr, and a treatment duration in the range of 0.5 to 30 minutes; The corona treatment comprises applying a power setting in the range of 20 to 300 W and a treatment duration in the range of 0.5 to 30 minutes, or The strong oxidizing solution includes a mixture of sulfuric acid (H2SO4) and hydrogen peroxide (H2O2) and the exposure duration ranges from 0.5 to 30 minutes.
13. The method of claim 1, further comprising adding liquid PDMS molecules onto the surface having the PDMS polymer grafted layer thereon.
14. An article comprising: A substrate having a surface having a PDMS polymer grafted layer on the surface, wherein each of the PDMS polymers has the formula: -Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-Q2 in: The Q1 is -O- or -O-(CH2) m -O- One of Q2 is -(-Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-) p -Q3 Q3 is -OH, -(CH2) m -OH, -Si(OH)3 or -(CH2) m -One of Si(OH)3 The m is an integer in the range of 0 to 10, Said n is an integer in the range of 10 to 500, Said p is an integer in the range of 0 to 500, and The Q1 is located at the end of the PDMS polymer covalently bonded to the surface, and The PDMS polymer grafted layer has a thickness ranging from 25 to 40 nm.
15. An article comprising: A substrate having a surface having a PDMS polymer grafted layer on the surface, wherein each of the PDMS polymers has the formula: -Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-Q2 in: The Q1 is -O- or -O-(CH2) m -O- One of Q2 is -(-Q1-Si(CH3)2-(O-Si(CH3)2-) n -O-Si(CH3)2-) p -Q3 Q3 is -OH, -(CH2) m -OH, -Si(OH)3 or -(CH2) m -One of Si(OH)3 The m is an integer in the range of 0 to 10, Said n is an integer in the range of 10 to 500, Said p is an integer in the range of 0 to 500, and The Q1 is located at the end of the PDMS polymer covalently bonded to the surface, and The PDMS polymer graft layer is formed on the surface of the substrate by the method according to any one of claims 1 to 13.
16. The article of claim 15, wherein the PDMS polymer grafted layer has a thickness value in the range of 10 to 40 nm.
17. The article of claim 14 or 15, wherein the treated surface having the PDMS polymer grafted layer thereon has a surface roughness of 1 nm or less.
18. The article of claim 14 or 15, wherein a water drop on the PDMS polymer grafted layer thereon has a contact angle hysteresis in the range of 0 to 5 degrees.
19. The article of claim 14 or 15, wherein the surface having the PDMS polymer grafted layer thereon further comprises liquid PDMS molecules located on the surface of the PDMS polymer grafted layer.
20. The article of claim 14 or 15, wherein the surface having the PDMS polymer grafted layer thereon is part of a pipe, a land, air or water vehicle, a window, a window cleaning blade, a wind turbine blade, a heat transfer device or an article of clothing.
Citation Information
Patent Citations
Preparation method of linear polydimethylsilane (PDMS) modified oil-water separation film, and oil-water separation film prepared through preparation method
CN109806780A